Il programma dell’ESA di osservazione della Terra - Cheli, Simonetta (GEOmedia, 2014)
The European Space Agency (ESA) operates a program of Earth observation since the launch of its first weather satellite, Meteosat, in 1977. Retracing the success of this first mission, the family of Meteosat satellites together with the missions ERS-1, ERS-2 and Envisat have provided a large amount of data about the Earth, its climate and climate change. The ESA is one of the largest providers of Earth Observation data to the scientific community within the framework of Earth Sciences.